Long-term outcomes and potential mechanisms of offspring exposed to intrauterine hyperglycemia - Yan, Yi-Shang; Feng, Chun; Yu, Dan-Qing; Tian, Shen; Zhou, Yin; Huang, Yi-Ting; Cai, Yi-Ting; Chen, Jian; Zhu, Miao-Miao; Jin, Min (Frontiers in Nutrition, 2023)
Diabetes mellitus during pregnancy, which can be divided into pregestational diabetes and gestational diabetes, has become much more prevalent worldwide. Maternal diabetes fosters an intrauterine abnormal environment for fetus, which not only influences pregnancy outcomes, but also leads to fetal anomaly and disease development in later life, like metabolic and cardiovascular diseases, neuropsychiatric outcomes, reproduction malformation and immune dysfunction. The underlying mechanisms are comprehensive and ambiguous, mainly focus on microbiota, inflammation, reactive oxygen species, cell viability and epigenetics. This review concluded the influence of intrauterine hyperglycemia on fetal structure development and organ function on later life and outlined potential mechanisms underpinning the development of adult diseases. Maternal diabetes leaves effect on generations and generations through gametes, more attention should be paid on prevention and treatment to rescue the pathological attacks of maternal diabetes to offspring.